A Mathematical Model of Horizontal Averaged Groundwater Pollution Measurement with Several Substances due to Chemical Reaction - Jirapud Limthanakul; Nopparat Pochai (My University, 2020)
Chloride is a well-known chemical compound that is very useful in industry and agricultural.Chloride can be transformed to hypochlorite, chlorite, chlorate and perchlorate, chloride and their substances are not dangerous if they are used in the optimal level.Groundwater containing contamination chloride and their substances impacts human health, for example, drinking water contaminated chloride exceed 250 mg/L can cause heart problems and lead to high blood pressure.To avoid this problem, we used mathematical models to explain groundwater contamination with chloride and their substances.Transient groundwater flow model provides the hydraulic head of groundwater.In this model we will get the level of groundwater, next, we need to find its velocity and direction by using the result in first model put into second model.Groundwater velocity model provides xand z-direction vector in groundwater, after computation we will plugin the result into the last model to approximate the chloride concentration in groundwater.Groundwater contamination dispersion model provides chloride, hypochlorite, chlorite, chlorate and perchlorate concentration.The proposed explicit finite difference techniques are used to approximate the model solution.Explicit method was used to solved hydraulic head model.Forward space described groundwater velocity model.Forward time and central space used to predict transient groundwater contaminated models.The simulations can be used to indicate when each simulated zone becomes a hazardous zone or a protection zone.
Keywords: Groundwater Pollution; Groundwater flow and contamination studies